Phase 2 study of preoperative chemotherapy with nab‐paclitaxel and gemcitabine followed by chemoradiation for borderline resectable or node‐positive pancreatic ductal adenocarcinoma - Emerson Y. Chen; Adel Kardosh; Nima Nabavizadeh; Bryan Foster; Skye C. Mayo; Kevin G. Billingsley; Erin W. Gilbert; Christian Lanciault; Aaron Grossberg; Kenneth G. Bensch; Erin Maynard; Eric C. Anderson; et al. (Cancer Medicine, 2023)
Abstract Background Neoadjuvant treatment with nab‐paclitaxel and gemcitabine for potentially operable pancreatic adenocarcinoma has not been well studied in a prospective interventional trial and could down‐stage tumors to achieve negative surgical margins. Methods A single‐arm, open‐label phase 2 trial (NCT02427841) enrolled patients with pancreatic adenocarcinoma deemed to be borderline resectable or clinically node‐positive from March 17, 2016 to October 5, 2019. Patients received preoperative gemcitabine 1000 mg/m2 and nab‐paclitaxel 125 mg/m2 on Days 1, 8, 15, every 28 days for two cycles followed by chemoradiation with 50.4 Gy intensity‐modulated radiation over 28 fractions with concurrent fluoropyrimidine chemotherapy. After definitive resection, patients received four additional cycles of gemcitabine and nab‐paclitaxel. The primary endpoint was R0 resection rate. Other endpoints included treatment completion rate, resection rate, radiographic response rate, survival, and adverse events. Results Nineteen patients were enrolled, with the majority having head of pancreas primary tumors, both arterial and venous vasculature involvement, and clinically positive nodes on imaging. Among them, 11 (58%) underwent definitive resection and eight of 19 (42%) achieved R0 resection. Disease progression and functional decline were primary reasons for deferring surgical resection after neoadjuvant treatment. Pathologic near‐complete response was observed in two of 11 (18%) resection specimens. Among the 19 patients, the 12‐month progression‐free survival was 58%, and 12‐month overall survival was 79%. Common adverse events were alopecia, nausea, vomiting, fatigue, myalgia, peripheral neuropathy, rash, and neutropenia. Conclusion Gemcitabine and nab‐paclitaxel followed by long‐course chemoradiation represents a feasible neoadjuvant treatment strategy for borderline resectable or node‐positive pancreatic cancer.